AN EFFICIENT PROTOPLAST ISOLATION PROTOCOL FOR TRANSIENT EXPRESSION IN RICE - Hilal Betul Kaya (Journal of Animal and Plant Sciences, 2025)
Genome editing technologies like CRISPR/Cas9 have revolutionized crop improvement; however, they remain challenging and genotype-dependent. Guide RNAs (gRNAs) are essential for genome editing but often struggle to efficiently cleave target loci due to complex chromatin structures and a lack of tools to predict target site accessibility. This leads to wasted time and resources on ineffective editing experiments, as in vitro assays do not account for the native genomic context. Protoplasts are valuable in plant genome editing research because they provide a rapid and efficient way to test various parameters and reagents, enabling scientists to optimize their editing strategies more quickly than through the time-consuming process of testing directly on whole plants, which often requires multiple growth cycles to observe genetic modifications. Rice, due to its economic significance and compact genome, serves as an ideal model for such studies. Despite ongoing efforts to optimize protocols for protoplast isolation and transfection in rice, achieving stable and high-yield protoplasts remains a challenge. This study presents a detailed protocol for rice protoplast isolation, emphasizing critical procedural steps. As a result, this study achieved a yield of approximately 1 x 108 protoplasts from 120 seedlings (5 x 107 protoplasts/mL) of the japonica rice cultivar Nipponbare, representing the highest protoplast yield reported to date. Additionally, PEG-mediated transfection efficiency reached 65% using the 35S: GFP construct.
Keywords: Protoplast isolation; rice; transfection; transient expression